2021
DOI: 10.1038/s41598-021-90349-6
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-modified liposomes triggered with ultrasound to treat HeLa cells

Abstract: Targeted liposomes are designed to target specific receptors overexpressed on the surfaces of cancer cells. This technique ensures site-specific drug delivery to reduce undesirable side effects while enhancing the efficiency of the encapsulated therapeutics. Upon reaching the tumor site, these liposomes can be triggered to release their content in a controlled manner using ultrasound (US). In this study, drug release from pegylated calcein-loaded liposomes modified with transferrin (Tf) and triggered with US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…In addition, dynamic light scattering (DLS) studies revealed the size range and % polydispersity (Pd) of the liposomes (Figure 1). The obtained Pd index value was found to be acceptable as it falls in the criteria of its upper limit of 20% for DLS measurements [51]. As shown in Table 1, even after 10 weeks of storage at 4 • C, the liposome solution was found to be stable, with minimal variation in their average radius (96.3 ± 3.9 nm), while maintaining a quenched load of calcein that was released upon the addition of Triton X-100, leading to a five-fold increase in the fluorescence signal.…”
Section: Characterization and Stability Analysis On Biotin-calcein Liposomesmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, dynamic light scattering (DLS) studies revealed the size range and % polydispersity (Pd) of the liposomes (Figure 1). The obtained Pd index value was found to be acceptable as it falls in the criteria of its upper limit of 20% for DLS measurements [51]. As shown in Table 1, even after 10 weeks of storage at 4 • C, the liposome solution was found to be stable, with minimal variation in their average radius (96.3 ± 3.9 nm), while maintaining a quenched load of calcein that was released upon the addition of Triton X-100, leading to a five-fold increase in the fluorescence signal.…”
Section: Characterization and Stability Analysis On Biotin-calcein Liposomesmentioning
confidence: 85%
“…The liposomes are a crucial component of the developed assay; hence, the preparation and characterization procedures of these nanocarriers are essential to ensure efficacy and reproducibility. Biotin-conjugated calcein-loaded liposomes were synthesized via the thin-film hydration method, similar to the previously reported studies [45,51], and a full characterization process was applied, including a Stewart assay, to quantify the total lipid concentration of the liposome solution, DSL measurements, and stability studies. The Stewart assay was conducted according to previously reported procedures [51], indicating a calculated total lipid concentration of 10.1 mmol/L.…”
Section: Characterization and Stability Analysis On Biotin-calcein Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study, calcein‐loaded liposomes functionalized with transferrin were used for the targeting of HeLa cells. Similarly, a synergistic effect between administration of LIFU and the targeting properties increased the therapeutic efficacy of the treatment [ 261 ]. A study on the concurrent use of LIFU and calcein‐loaded liposomes functionalized with human serum albumin for site-specific breast cancer therapy demonstrated similar results [ 262 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, their phagocytosis in the blood circulation is still challenging [252]. Liposomes can also be targeted via surface ligands in order to maximize the efficacy of cargo delivery and minimize systemic side effects [260][261][262].…”
Section: Liposomesmentioning
confidence: 99%